A randomized controlled clinical trial on the effect of acupuncture therapy in dairy cows affected by pyometra. (December 2020) - Pinedo, P.J.; Caixeta, L.S.; Barrell, E.A.; Velez, J.; Manriquez, D.; Herman, J.; Holt, T.
Abstract: Pyometra (PYO) is a reproductive disease characterized by the accumulation of purulent or mucopurulent material within the uterine lumen, in the presence of an active corpus luteum (CL). As the CL continues secreting progesterone, PYO would develop following endometritis. Due to prohibited use of artificial luteolytic hormones in US certified organic dairies, conventional therapies consisting of administration of prostaglandin F2α, are not applicable. The objective of this study was to evaluate the efficacy of two acupuncture procedures on the treatment of persistent CL in cows with PYO. We hypothesized that acupuncture would reduce CL diameter and serum progesterone (P4) concentrations, leading to regression of PYO. Holstein cows with PYO, at an USDA certified organic dairy farm in Northern Colorado, were enrolled in a randomized controlled clinical trial and assigned to 1 of 3 treatments: (1) control pyometra (CP; no treatment; n  = 17); (2) electroacupuncture (EAP; n  = 15); and (3) laser acupuncture (LAP; n = 15). Each cow received three 9-min (EAP) or 20-min (LAP) acupuncture sessions in alternate days. All study cows had blood samples collected for determination of serum progesterone concentration at d0, and at d2, d4, d11, d18, and d25 after first treatment. The ovaries were scanned by transrectal ultrasonography at -3d, d0, d2, d4, d11, and d18 to determine the diameter of the CL. The effect of treatment in the outcome variables was evaluated by ANOVA and by repeated measures analyses, accounting for baseline data (CL diameter and progesterone serum concentration). Average ± SE change in CL diameter from d0 to d18 were 0.94 ± 1.0 mm, 0 ± 1.0 mm, and − 0.33 ± 1.0 mm for CP, EAP, and LAP, respectively. The repeated measures analysis indicated no significant differences for CL diameter among groups. None of the study cows had serum progesterone values <1 ng/ml by the end of the monitoring period (d25) and average ± SE change from d0 to d25 were − 4.0 ± 1.97 ng/ml, −0.76 ± 2.1 ng/ml, and 3.24 ± 1.9 ng/ml for CP, EAP, and LAP, respectively. The repeated measures analysis indicated no significant differences for serum progesterone concentrations among groups. On farm cow records reviewed 150 d after treatment indicated that 2 cows in EAP and 1 cow in LAP conceived 38 d, 68 d, and 38 d, after treatment completion. In conclusion, acupuncture was not an effective treatment for persistent CL in cows with PYO, during the monitoring period. Highlights: Pyometra is a reproductive condition seriously affecting cow fertility. Due to prohibited use of artificial luteolytic hormones in USA certified organic dairies, conventional therapies consisting of administration of prostaglandin F2α, are not applicable. A randomized controlled clinical trial on the effect of acupuncture therapy in dairy cows affected by pyometra was performed. Acupuncture was not an effective treatment for persistent CL in cows with PYO, during the monitoring period.